Polysaccharide-Based Nanogels to Overcome Mucus, Skin, Cornea, and Blood-Brain Barriers: A Review - Ju Wang; Marco Viola; Claudia Migliorini; Luca Paoletti; Silvia Arpicco; Chiara Di Meo; Pietro Matricardi (Pharmaceutics, 2023)
Nanocarriers have been extensively developed in the biomedical field to enhance the treatment of various diseases. However, to effectively deliver therapeutic agents to desired target tissues and enhance their pharmacological activity, these nanocarriers must overcome biological barriers, such as mucus gel, skin, cornea, and blood-brain barriers. Polysaccharides possess qualities such as excellent biocompatibility, biodegradability, unique biological properties, and good accessibility, making them ideal materials for constructing drug delivery carriers. Nanogels, as a novel drug delivery platform, consist of three-dimensional polymer networks at the nanoscale, offering a promising strategy for encapsulating different pharmaceutical agents, prolonging retention time, and enhancing penetration. These attractive properties offer great potential for the utilization of polysaccharide-based nanogels as drug delivery systems to overcome biological barriers. Hence, this review discusses the properties of various barriers and the associated constraints, followed by summarizing the most recent development of polysaccharide-based nanogels in drug delivery to overcome biological barriers. It is expected to provide inspiration and motivation for better design and development of polysaccharide-based drug delivery systems to enhance bioavailability and efficacy while minimizing side effects.